The neutral and nearly neutral theories of molecular evolution 1 - Bielawski, Joseph P. (Henry Stewart Talks, 2022)
Introduction to theories of natural genetic diversity, Within-species genetic polymorphism, Between-species genetic divergence, Fundamental processes of evolution, Mutation, Natural selection, Genetic drift, Neo-Darwinism, Neutral model